Police misconduct complaint investigations manual - Attard, Barbara (Routledge series on practical and evidence-based policing, 2021)
"The Police Misconduct Complaint Investigations Manual provides a timely and unique, step-by-step approach to conducting or reviewing police misconduct investigations, whether a complaint involves a lower level allegation of discourtesy or more serious concerns such as excessive force or criminal behavior. Utilizing real-life examples and updated case law to illustrate points, it provides best practices for investigating police action resulting in misconduct complaints. The Manual's comprehensive approach includes detailed procedures and policy considerations from intake through case closure, and discusses data tracking, reporting on trends, selecting and training investigative staff, civilian oversight, and a host of special issues that can arise with police misconduct complaints. The Manual is suitable for both sworn personnel and civilians handling or reviewing investigations and whether working internally for a police department or externally in oversight or another capacity. The guidance provides detailed examples of witness interview questions and types of evidence to collect, with discussion on making difficult credibility determinations and approaches to analyzing the information gathered to arrive at a recommended finding. Review questions are found at the end of most chapters, for use in academic or investigative training environments. Police officers engaged in the often complex and challenging work of public safety deserve and expect objective, thorough, and timely handling of complaints. Complainants and other stakeholders seek accountability and transparency when an officer behaves in a way that raises questions about their professionalism. The Complaint Investigations Manual provides instruction on handling misconduct complaints in a manner that will ensure the goals of law enforcement and stakeholders are met. The authors intentionally use a broad approach to make the Manual relevant and easy to use by law enforcement personnel, civilians in oversight or other capacities who work on police misconduct matters, and the criminal justice academic community. It is a critical primer for internal affairs investigators, police managers, law enforcement leaders, auditing professionals, civilian oversight practitioners, government representatives, community advocates, criminal and social justice students, and all others in pursuit of fair, thorough, and timely investigations of police misconduct complaints"--